2008
DOI: 10.5194/aab-51-255-2008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in selected physicochemical parameters of breast muscles of geese from Polish conservation flocks depending on duration of the post slaughter period

Abstract: In four Polish conservative flocks of Suwałki (Su), Kartuzy (Ka), Kielce (Ki) and L* 24h ) and EC 45' (3.23 mS/cm). The pH value and L* and a* parameters (except L* 24h and a* 24h ) of the analysed flocks were decreasing, and conductivity increasing together with the time post slaughter, and the rate of changes depended on the birds' origin. Greater differences between pH values, measured 15 min and 24 h after slaughter were stated in breast muscles from Ka (1.09) and Su (0.90) geese than from the other two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
2
9
2
Order By: Relevance
“…The pH value of the breast meat in the present study was similar to the pH value determined by Okruszek et al . (); however, it was much lower than the pH value determined by Liu et al . ().…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The pH value of the breast meat in the present study was similar to the pH value determined by Okruszek et al . (); however, it was much lower than the pH value determined by Liu et al . ().…”
Section: Resultscontrasting
confidence: 62%
“…Okruszek et al . () found that pH values of the Polish geese varied between 5.65 and 5.96 depending on the type of the goose, while the pH values of the breast meat of Yangzhou geese varied from 6.20 to 6.30 (Liu et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al 30 reported that in Cherry Valley ducks cooking loss was 38.10%, and drip loss was 7.48%. In our study we found no relationship between the sex of ducks or their diet and the pH of breast muscles, which according to literature data is in the range of 5.65–6.20 and depends on the level of glycogen reserves in muscles 27 , 31 , 32 . The value of pH decreases post-mortem due to the increased concentration of lactic acid in muscles, and this process determines meat quality.…”
Section: Discussionsupporting
confidence: 53%
“…In the leg muscles there was a greater share of type IIB fibres. A decrease in pH significantly increases conductivity in the breast muscles (Okruszek et al, 2008). The share of red fibres (βW) in W33 bird breast muscles was reported to be greater than in W11 birds, while the share of white fibres (αW) in W33 and W11 males was 22.1 and 20.9%, and in females 22.5 and 25.9%, respectively.…”
Section: Physicochemical Properties Of Meatmentioning
confidence: 93%